Preventive Health Insights: The Correlation of Junk Food Intake and Sleep Quality with Dysmenorrhea: Studi Potong Lintang pada Remaja Putri di Kota Palu, Indonesia - Lilik Sofiatus Solikhah; Raehani Raehani; Ni Ketut Kariani (Poltekkes Kemenkes Jambi, 2025)
Background: Dysmenorrhea is a prevalent gynecological problem among adolescent girls, often influenced by modifiable lifestyle factors such as diet, sleep quality, and nutritional status. This study aimed to examine the association of junk food consumption, sleep quality, and nutritional status with dysmenorrhea among female students. Methods: A cross-sectional study was conducted among 169 female students at SMKN 1 Palu, Indonesia. Data were collected using validated questionnaires: Food Frequency Questionnaire (FFQ) for junk food intake, Pittsburgh Sleep Quality Index (PSQI) for sleep quality, and BMI-for-age for nutritional status. Dysmenorrhea severity was assessed using the Numeric Rating Scale (NRS). Data were analyzed using Chi-square and Spearman tests. Results: The findings revealed that poor sleep quality was significantly associated with dysmenorrhea (p = 0.038), while junk food consumption (p = 0.646) and nutritional status (p = 0.426) showed no significant association. Conclusion: Sleep quality emerged as a modifiable determinant of dysmenorrhea, suggesting that improving sleep hygiene may help alleviate menstrual pain among adolescents. Integrated health promotion strategies that combine sleep education and balanced nutrition are recommended for adolescent reproductive health programs.